Obvladovanje sladkorne bolezni v okviru m-zdravja - Vrbnjak, Dominika (Informatica Medica Slovenica, 2015)
The article provides an overview of the diabetes mellitus management within mHealth. In the introduction, the key terms are defined and mHealth and diabetes mellitus br iefly described. Next, a variety of foreign and domestic solutions and services of mHealth and mobile applications for diabetes mellitus management are reviewed. The results of the use of such services are highlighted, and a summary of their advantages and disadvantages is given. In conclusion, the possibilities for further research in this area and the future of diabetes mellitus management within mHealth are described.
Keywords: e-zdravje; mobilne aplikacije; m-zdravje; Sladkorna bolezen; telemedicina; telezdravstvo